2013
DOI: 10.1021/mp300665u
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Oxidation Sites and Covalent Cross-Links in Metal Catalyzed Oxidized Interferon Beta-1a: Potential Implications for Protein Aggregation and Immunogenicity

Abstract: Oxidation via Cu2+/ascorbate of recombinant human interferon beta-1a (IFNβ1a) leads to highly immunogenic aggregates, however it is unknown which amino acids are modified and how covalent aggregates are formed. In the present work we mapped oxidized and cross-linked amino acid residues in aggregated IFNβ1a, formed via Cu2+/ascorbate catalyzed oxidation. Size exclusion chromatography (SEC) was used to confirm extensive aggregation of oxidized IFNβ1a. Circular dichroism and intrinsic fluorescence spectroscopy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…Reactive oxygen species responsible for oxidation of therapeutic proteins may originate from light exposure, reactive oxygen species formed in combination with surfactants such as polysorbate, and transition metals, for example, from the cell culture medium or the equipment used for bioproduction . Besides inactivation, products formed during oxidation of proteins may lead to the formation of noncovalent or covalent aggregates or colored by‐products …”
Section: Desired Molecular Features and Test Methods Used During Devementioning
confidence: 99%
“…Reactive oxygen species responsible for oxidation of therapeutic proteins may originate from light exposure, reactive oxygen species formed in combination with surfactants such as polysorbate, and transition metals, for example, from the cell culture medium or the equipment used for bioproduction . Besides inactivation, products formed during oxidation of proteins may lead to the formation of noncovalent or covalent aggregates or colored by‐products …”
Section: Desired Molecular Features and Test Methods Used During Devementioning
confidence: 99%
“…23,25,40,60,62 Moreover, all of these aggregates showed some oxidation of histidine 61,63 and the aromatic amino acid residues. 63,64 Hydrogen peroxide-mediated oxidation, 21,40 stirring 61 and UV-light exposure 22,24,28 have also been used to generate protein aggregates which have enhanced immunogenicity in the murine model system tested compared to that of the protein before stress treatment. It is important to note that all of the chemical modifications described above were induced by treatments that increased the amount of such modifications to levels that and are not representative of what typically would be seen in the clinic.…”
Section: Effects Of Product-related Factors On Immunogenicitymentioning
confidence: 99%
“…Although oxidation of His, primarily by metal-catalyzed oxidation, has been shown for several proteins and peptides (Chang et al, 1997;Ji, Zhang, Cheng, & Wang, 2009;Khossravi et al, 2000;Li, Nguyen, et al, 1995;Levine, 1983;Rippa & Pontremoli, 1968;Torosantucci et al, 2013;Uchida & Kawakishi, 1990;Yamagata, Takahashi, & Egami, 1962;Zhao et al, 1997), the literature is sparse on examples of oxidation of histidine in mAbs. Recently it was shown in the copper-catalyzed oxidation of an IgG2 mAb that His residues in the Fc portion of the antibody were oxidized , and it was suggested that this oxidation may be linked to the production of immunogenic aggregates (Joubert, Luo, Nashed-Samuel, Wypych, & Narhi, 2011).…”
Section: His Oxidation In Mabsmentioning
confidence: 99%